PHYSICAL THERAPY OR SURGERY FOR LUMBAR STENOSIS: ASSOCIATING FACTORS AND HEALTHCARE UTILIZATION. (11th November 2018) - Schmidt, C; Mor, V; Resnik, L; Ogarek, J
Abstract: Medicare spending associated with lumbar spinal stenosis (LSS) continues to increase. Physical therapy (PT) is associated with less healthcare utilization for patients with low back pain. However, little is known about factors associated with the selection of PT versus surgery and subsequent healthcare consumption for patients with LSS. This research will identify factors associated with receiving PT or surgery and quantify the impact of PT on additional healthcare utilization after incident LSS diagnosis. This research is critical to understanding long term implications of early care plan decisions and the impact on subsequent medical risk following a diagnosis of LSS. A retrospective analysis of Medicare claims data for beneficiaries diagnosed with incident LSS during 2008 was conducted. Two groups were identified based on the first intervention received following incident diagnosis: PT or surgery. Two-year healthcare outcomes included: hospitalizations, spinal injections, advanced imaging, and narcotic use. Incident LSS diagnosis was 75, 551 (0.8%) with 3, 069 (4%) in the PT group and 9, 195 (12%) in the surgery group. On average, younger beneficiaries with low back pain, degenerative disc disease, and narcotics without cardiopulmonary disease were associated with having surgery. Beneficiaries with asthma, ischemic heart disease, depression and hearing impairment were associated with receiving PT. Beneficiaries receiving PT as an initial intervention were less likely to receive spinal injections, advanced imaging and narcotics and more likely to be hospitalized two-years following LSS diagnosis. Findings may inform future clinical trials evaluating early intervention decisions and healthcare system efforts to contain rising costs for patients with LSS.